An Ecological Exploration on Poudyal’s The Parrot in a Cage - Pokhrel , Mohan Kumar (Dristikon: A Multidisciplinary Journal, 2026)
This study analyzes The Parrot in a Cage of Lekhnath Poudyal through the lens of ecocriticism. The cage is the symbol of the suppressed voice of humans in the Nepalese society. The major objectives of this analysis are to identify the caged parrot of Paudyal to depict exploitation in ecology and highlight the worth of an ecocritical reading; to examine how captivity and alienation imagery, along with critical perspectives, shows connections between independence of humans. The researcher uses the theory of Arne Naess to interpret the primary text from the perspective of ecocriticism. The theorist explicates that destroying a portion of nature affects the whole eco-system. The results unveils that the parrot’s custody reveals political suppression. It manifests alienation in ecology, the voices of non-human beings, and the destruction of nature due to irresponsible activities of people. The discussion mentions how earlier criticism emphasized exploitation in politics but neglected readings based on ecology, referring a gap that this analysis links human freedom with ethics in ecology. The conclusion highlights that the text reveals a cultural symbol of conflict and an ecological meditation, asserting the moral responsibility of humans toward freedom and contract in environment. By analyzing the text from the lens of ecocriticism, this research depicts its significance to discussions on ecology and the duty of human beings.